Concurrency Phenomenon in law of obligations. Contribution Quotas among debtors as a systemic problem (Nueva Epoca, 2020)
The concurrent obligations had express norma- tive recognition in three articles of the Civil and Commercial National Code (art. 850, 851 and 852), where it is regulated as a result of the jurisprudential criteria evolution that mainly solved the problem of compulsory law generated by the expansion of the responsible on various liability hypotheses. In this context, and 5 years after the enactment of the Civil and Commercial Code, the imposition of various contribution quotas among the concurrent debtors has been reserved for return actions, by marginalizing said discussion of the main process and therefore its deferral.This is the center of the analysis of the article, where it is proposed to understand the determi- nation of the contribution quota as an expression of the duty to sentence in a reasonably substantiate a ruling (art. 3 of the CCyCN).
Keywords: obligations of plural subject; concurrent obligations; contribution quota of the concurrent debtors; duty to found sentences; plurality of source cause; uniqueness of object; causal incidence in the concurrence